Dampak kesenjangan antara penerimaan dan penyaluran dana zis terhadap rpogram-program LAZNAS Al-Azhar - Dinda Ratnasari; Suherman Rosyidi (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study’s purpose is to find out how LAZNAS Al-Azhar’s programs is affected by the gap between the collection and distribution of ZIS funds. The gap’s effects is identified by using the four aspects of zakat institution performance indicators which is input, process, output, and quality  within the interview questions. This study uses a qualitative approach with a case study strategy. Data collection is done through interviews with informen, direct observation, and documentation to the research object. The analytical technique used is qualitative descriptive, namely by narrating and describing the results of interviews and direct observation. The study’s results are the impacts arising from the gap between the collection and distribution of ZIS funds to the sustainability of LAZNAS Al-Azhar’s programs which is LAZNAS Al-Azhar running large value programs with bailout funds in advance, LAZNAS Al-Azhar carries out routine programs such as assistance programs for orphans with bailout funds in advance as well. Programs which the funds are collected first before being distributed are assistance programs for affected areas or scholarship programs. LAZNAS Al-Azhar has tried to minimized the gap that has occurred with not to hold the funds collected for too long policy. The funds that have been collected will soon be channeled through programs in the community.Keywords: Gap, Zakat, Collection, Distribution, Performance. REFERENCESAfifuddin dan Beni Ahmad Saebani. 2012. Metodologi Penelitian Kualitatif. Bandung : CV Pustaka Setia.Ali, Mohammad Daud. 1988. Sistem Ekonomi Islam: Zakat dan Wakaf. Jakarta : Universitas IndonesiaAl-Ba’ly, Abdul Al Hamid Mahmud. 2006. Ekonomi Zakat: Sebuah Kajian Moneter dan Keuangan Syariah. Jakarta : Raja Grafindo Persada.Al-Zuhayly, Wahbah. 1995. Zakat Kajian Berbagai Mazhab. Bandung: PT Remaja RosdakaryaArikunto, Suharsimi. 2006. Prosedur Penelitian. Jakarta: PT Rineka Cipta.Ash-Shawi, Shalah dan Abdullah Al-Mushlih. 2015. Fikih Ekonomi Islam. Darul Haq : JakartaAswayni, Qalbie Rianta. 2017. Analisis Ketidakefektifan Distribusi Dana Zakat di Kabupaten Sidoarja. (Studi kasus : BAZNAS Kabupaten Sidoarjo dan LAZNAS YDSF Kabupaten Sidoarjo.). Skripsi Sarjana Ekonomi Universitas Airlangga SurabayaAzis, dkk. 2017. Zakat & Pemberdayaan. Surabaya: Pusat Penerbitan dan Percetakan Universitas Airlangga.Basri, Hasan. 2010. Manajemen Zakat: Menuju ke Arah Profesionalisasi. (Online),(http://kanazakat.blogspot.com/2011/07/manajemen-zakat.html , Diakses 21 Oktober 2018)BAZNAS, 2016. Outlook Zakat Indoneisa 2017. Jakarta_______, 2015. Outlook Zakat Indoneisa 2016. JakartaBeik, Irfan Syauqi. 2008. Pro Ekonomi Syariah Pro Rakyat. Jakarta: RepublikaBungin, Burhan. 2008. Analisis Data Penelitian Kualitatif Pemahaman Filosofis dan Metodologis ke Arah Penguasaan Model Aplikasi. Jakarta : Raja Grafindo Persada.Chaudry, Muhammad Syarif. 2014. Sistem Ekonomi Islam Prinsip Dasar. Jakarta: Kencana Prenadamedia GroupDjuanda, Gustian dkk. 2006. Pelaporan Zakat Pengurang Pajak Penghasilan. Jakarta: Raja Grafindo Persada.Fauzia, Amelia. 20013. Faith and The State: a History of Islamic Philantrophy in Indonesia. Leiden: Brill Academic Publishers. hlm. 175Hafidhuddin, Didin. 2002. Zakat Dalam Perekonomian Modern. Jakarta: Gema InsaniHalim, Abd, dkk. 2011. Zakat Collection – Distribution Gap: A measure of Effectiveness in The Management of Zakat. Makalah disajikan dalam Seminar Zakat Internasional, Bogor, 19-21 Juli 2011Halim, Abd, dkk. 2015. “Efficiency of Islamic Institutions: Empirical Evidence of Zakat Organizations’ Performance in Malaysia”. Journal of Economics, Business and Management, Vol. 3, No. 2.Hasan, M. Ali. 1996. Zakat, Pajak Asuransi dan Lembaga Keuangan. Jakarta: Raja Grafindo Persada.Huda, Nurul dan Novarini. 2015. Zakat Perspektif Mikro-Makro Pendekatan Riset. Jakarta: Kencana Prenadamedia Group.http://baznas.go.id/, diakses pada tanggal 20 Mei 2018Inayah, Gazi. 2003. Teori Komprehensip Tentang Zakat dan Pajak. Yogyakarta: Tiara Wacana Yogya.Indriyanti, Amanda Nuri. 2016. Analisis Overlapping (Tumpang Tindih) Distirbusi Zakat Pada LAZ di Surabaya. Skripsi Sarjana Ekonomi Universitas Airlangga SurabayaMahfud, Rois. 20011. Al-Islam: Pendidikan Agama Islam. Jakarta: Penerbit ErlanggaMoleong, Lexy J. 2001. Metode Penelitian Kualitatif Edisi Revisi. Bandung: Remaja Rosda KaryaMufraini, Arif. 2006. Akuntansi dan Manajemen Zakat: Mengomunikasikan kesadaran dan Membangun Jaringan. Jakarta : Kencana Prenada media GroupNasution, Mustafa Edwin dkk. 2015. Pengenalan Eksklusif Ekonomi Islam. Jakarta: Kencana Prenadamedia GroupQardhawi, Yusuf. 1999. Hukum Zakat. Bandung: Pustaka Mizan._______. 2010. Shadaqah Cara Islam Mengentaslan Kemiskinan. Bandung: PT Remaja RosdakaryaRozalinda. 2015. Ekonomi Islam Teori dan Aplikasinya pada Aktivitas Ekonomi. Jakarta: Raja Grafindo Persada.Ryandono, Muhammad Nafik Hadi. 2008. Ekonomi ZISWAQ (Zakat, Infiaq, Shadaqah, dan Wakaf). Surabaya: IFDI dan CenforisSari, Dian Permata. 2012. Penyebab Kesenjangan Antara Pengumpulan dan Pendistribusian Dana Zakat pada Rumah Cabang Zakat Surabaya. Skripsi Sarjana Ekonomi Universitas Airlangga SurabayaShihab, Quraish. 2001. Tafsir Al-Mishbah jilid 15. Tangerang Selatan : Lentera Hati.Sudirman. 2007. Zakat dalam Pusaran Arus Modernitas. Malang: UIN-Malang Press.Sugiyono. 2015. Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: AlfabetaSulistyo-Basuki. 2006. Metode Penelitian. Jakarta: Wedatama Widya Sastra dan Fakultas Ilmu Pengetahuan Budaya Universitas IndonesiaSyamil Al-Quran Miracle The Reference. 2010. Bandung: Sygma Publishing.Ibnu Katsir, Tafsir Qur’an, 2015. hlm 5Ritonga, A. Rahman dan Zainuddin MA. 1997. Fiqih Ibadah. Jakarta:Radar Jaya Pratama.Shihab, Al-Misbah. Tafsir Qu’ran. 2009. Hlm 350Tim Divisi Kepatuhan dan Kajian Dampak LAZ Al-Azhar. 2017. Panduan Zakat Lembaga Amil Zakat Al-Azhar. Jakarta : Lembaga Amil Zakat Nasional Al-Azhar.Undang-Undang Republik Indonesia No. 23 Tahun 2011 Tentang Pengelolaan Zakat.Widiastuti, Tika dan Suherman Rosyidi. 2015. Model dalam pendayagunaan zakat produktif oleh lembaga zakat dalam meningkatkan pendapatan mustahiq. Surabaya: Universitas AirlanggaYin, Robert K. 2002. Studi Kasus Desain dan Metode. Jakarta: PT. Raja Grafindo PersadaYin, Robert K. 2009. Studi Kasus, Desain dan Metode Ed 1. Jakarta: Rajawali Press.www.alazharpeduli.org, diakses tanggal 2 Februari 2018www.dompetdhuafa.org diakses tanggal 4 Mei 2018www.republika.co.id diakses tanggal 28 Mei 2018ww.pusat.baznas.go.id  diakses tanggal 28 Mei 2018.